Periplocin potentiates ferroptotic cell death in non-small cell lung cancer by inducing the degradation of Nrf2 - Jinhao Wang; Yue Zhu; Jialiang Song; Fengping Yang; Peng Wang; Ziyi Zhang; Yuxuan Li; Minghe Dai; Yinuo Wang; Waleed Yousuf; Jiayu Li; Dian Yang; et al. (Cancer Cell International)
Abstract Background Non-small cell lung cancer represents the main histological subtype of lung cancer. Periplocin is a major cardiac glycoside found in the traditional Chinese medicine Cortex periplocae administered in cardiovascular and autoimmune diseases. Inspired by recent findings reporting the anticancer activities of periplocin, this study investigates its potential effects against lung cancer. Methods The influence of periplocin on non-small cell lung cancer cells was examined by CCK-8, colony formation, and EdU staining assays, followed by transcriptomic profiling with RNA sequencing. Gene set enrichment analysis was conducted to identify pathways affected by periplocin. Nrf2 expression was assessed by Western blotting and turnover was investigated by cycloheximide chase assays. Cellular ferroptosis was induced by the GPX4 inhibitor with or without periplocin treatment. The in vivo effects of periplocin were assessed using lung cancer xenograft mouse models. Results Periplocin inhibited lung cancer cell growth in vitro. Transcriptomic analysis showed significant downregulation of Nrf2 downstream targets. Biochemical characterization revealed that periplocin increased Nrf2 turnover by promoting proteasomal degradation, leading to decreased levels of downstream transcripts. Functionally, Nrf2 reduction imposed by periplocin treatment rendered lung cancer cells increased susceptibility to ferroptosis induction. Finally, periplocin treatment demonstrated similar inhibition to restrict lung cancer xenograft growth as compared to the ferroptosis inducer imidazole ketone erastin, with both compounds leading to elevated expression of the ferroptosis marker COX2 in xenograft tumor tissues. Conclusion Our investigation suggests periplocin as a potential agent in the development of ferroptosis-inducing therapies against non-small cell lung cancer. Graphical abstract